2022
DOI: 10.3390/vaccines10101576
|View full text |Cite
|
Sign up to set email alerts
|

The Longitudinal Analysis on the Anti-SARS-CoV-2 Antibodies among Healthcare Workers in Poland—Before and after BNT126b2 mRNA COVID-19 Vaccination

Abstract: One of the groups most vulnerable to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is healthcare workers (HCWs) who have direct contact with suspected and confirmed coronavirus diseases 2019 (COVID-19) patients. Therefore, this study aimed to (i) conduct a longitudinal analysis of the seroprevalence of SARS-CoV-2 infection among HCWs working in two healthcare units (HCUs) in Poland and (ii) identify anti-SARS-CoV-2 IgG antibody (Ab) response factors following infection and anti-COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…However, due to their medical background, the lecturers involved in our study were also involved in fighting the pandemic, e.g., in molecular diagnostics of SARS-CoV-2 infection. Our previous study showed that HCWs are at the highest risk of SARS-CoV-2 infection and are characterised by the highest seroprevalence among the occupational groups [ 45 ]. Further, other authors have demonstrated the clinical work environment as a key SARS-CoV-2 infection risk factor [ 46 , 47 ] but have also highlighted that local COVID-19 foci and household contacts may affect seropositivity rates [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to their medical background, the lecturers involved in our study were also involved in fighting the pandemic, e.g., in molecular diagnostics of SARS-CoV-2 infection. Our previous study showed that HCWs are at the highest risk of SARS-CoV-2 infection and are characterised by the highest seroprevalence among the occupational groups [ 45 ]. Further, other authors have demonstrated the clinical work environment as a key SARS-CoV-2 infection risk factor [ 46 , 47 ] but have also highlighted that local COVID-19 foci and household contacts may affect seropositivity rates [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Post-vaccination antibodies were found in 68 of the 69 analysed HCWs, and the prevalence of anti-SARS-CoV-2 S antibodies increased from 84.50% in September 2021 [12] to 98.56% in November 2022. Among these HCWs, there was one individual with a complete depletion of anti-SARS-CoV-2 S antibodies.…”
Section: Prevalence Of Anti-sars-cov-2 Antibodies Among Healthcare Wo...mentioning
confidence: 97%
“…Seven individuals had developed anti-SARS-CoV-2 NCP antibodies without declaring COVID-19 in their history. The prevalence of anti-SARS-CoV-2 NCP antibodies increased from 5.71% in September 2021 [12] to 39.1% in November 2022.…”
Section: Prevalence Of Anti-sars-cov-2 Antibodies Among Healthcare Wo...mentioning
confidence: 97%
See 2 more Smart Citations